Self-Assembled Polyaniline Nanotubes with Rectangular Cross-Sections - Ding, Zhongfen; Currier, Robert P.; Zhao, Yusheng; Yang, Dali (Macromolecular chemistry and physics, 2009)
Nanomaterials made from the conducting polymer polyaniline (PANI) have very unique applications due to their high surface area and ease of processing. The link between synthesis conditions and morphology of PANI nanomaterials has been the subject of numerous investigations in recent years. Formation mechanisms for different morphologies have also been proposed. In this work, we report a self‐assembly method to make high yield PANI nanotubes with rectangular holes and outer contours by qualitatively and purposely controlling reaction rate. We find that aggregation of detectable and separable reaction intermediates is directly correlated with PANI nanotubes formation, consistent with the observation of oligoaniline precipitates reported in the literature. Control over intermediate aggregates morphology is studied systematically. By controlling the reaction rate through adjusting acid and oxidant concentrations, we can slow down the aggregation rate of the intermediates to largely enhance the yield of nanotubes with rectangular cross‐sections. To understand the correlation between the intermediates aggregation and the morphology of the resulting PANI tubes, the morphologies of intermediate aggregates and final nanotubes were characterized using SEM, STEM, and TEM. Open circuit potential (OCP) was used to monitor the polymerization process. Molecular weight distribution results were also obtained for the intermediate aggregates and the final products. Based on our study, we propose a simple PANI nanotube formation mechanism. High yield polyaniline NTs with rectangular holes synthesis using the chemical oxidative polymerization method is presented. The NTs formation goes through an intermediates aggregation step. The morphologies of intermediate aggregates are affected by reaction kinetics, which can in turn be qualitatively controlled by adjusting the initial molar concentration ratio of the reactants.